TYPES OF EDUCATIONAL BUSINESS GAMES - Druz, Yu.M. (Pedagogy of Higher and Secondary Education, 1999)
The article describes different types of business-like games, divided in accordance with their didactic purposes. The author gives the analyses of the mentioned types of games and shows in details the methods of acting at different stages of teaching and training o f new material, throws student’s and teacher’s role in them, gives the criteria of an estimation of game’s results and turns readeґs attention to the methods of stimulation of activities of all participants. The content and the structure of games are determined in accordance with didactic aims of the lessons, but all the games are oriented on the future professional activity of students and at the same time they are completely answered the training course.